Abundances of C, N, and O in AGB Giants and Model Atmospheres. Issue Volume 14:Issue S343(2019) (August 2018) - Aringer, B.; Marigo, P.; Nowotny, W.; Girardi, L.; Mečina, M.; Nanni, A.
Abstract: Based on hydrostatic models we discuss the effects of molecular opacities and abundance changes concerning C, N or O on the atmospheric structures, spectra and photometric properties of C/M AGB giants.